The sage Apollonius of Tyana in Alexandria: the view of the Greek sophist Philostratus about the capital of the Roman province of Egypt (third century AD) - Silva, Semíramis Corsi (Romanitas - Revista de Estudos Grecolatinos, 2014)
This paper aims to interpret specific passages of the book V of the biographical work The Life of Apollonius of Tyana, written by the Greek sophist Flavius ​​Philostratus in the mid-third century A.D. We intend to demonstrate how a Greek sophist, inserted in the structures of power in the Roman Empire at the time of the Severan dynasty, perceived the city of Alexandria through the analyses of the relations established by his personage, the sage traveler Apollonius, who used to stay at this space. Furthermore, we intend to discuss if the trip to Alexandria was real or a creation by the writer, reflecting about the perspective and aspirations of Philostratus.